Platinum(iv) azido complexes undergo copper-free click reactions with alkynes. Issue 31 (26th February 2018) - Farrer, Nicola J.; Sharma, Gitanjali; Sayers, Rachel; Shaili, Evyenia; Sadler, Peter J.
Abstract : We report our investigations into the first examples of copper-free 1, 3-dipolar cycloaddition (click) reactions of electrophiles with a Pt(iv ) azido complex. Abstract : We report our investigations into the first examples of copper-free 1, 3-dipolar cycloaddition (click) reactions of electrophiles with a Pt IV azido complex. The Pt- IV azido complex trans, trans, trans -[Pt IV (py)2 (N3 )2 (OH)2 ] (1 ) was reactive towards dimethyl acetylenedicarboxylate (DMAD) (2 ), diethyl acetylenedicarboxylate DEACD (3 ), N -[(1 R, 8 S, 9 s )-bicyclo[6.1.0]non-4-yn-9-ylmethyloxycarbonyl]-1, 8-diamino-3, 6-dioxaoctane (BCN) (11 ) and dibenzocyclooctyne-amine (DBCO) (12 ) resulting in formation of the corresponding mono (a) and bis-substituted (b) complexes. Complexes of2 undergo further reactions between the Pt centre and the carbonyl group to form2a′ and2b′ . This is not seen for the products of the corresponding Pt II azido complex trans -[Pt(py)2 (N3 )2 ] with acetylene2 . Novel complexes2a′, 2b′, 11a and11b have been characterised by multinuclear NMR, IR and UV-vis spectroscopy and ESI-MS. These reactions represent new synthetic routes to novel Pt(iv ) complexes.